Impacts of Salmonid Fish Production on River Water Quality: A Critical Appraisal of the Evidence - Anna N. S. Michalopoulou; Nic R. Bury; Robert A. Holland; Imogen Speck; Tim Sykes; Gail Taylor; Marc G. Dumont; Kelvin S.‐H. Peh (Reviews in Aquaculture, 2026)
Rivers are recognised as providing valuable goods and services to society, and as hotspots of global biodiversity. Fish farming is an economically important activity associated with river systems; however, the effects of this industry on river health are not entirely understood. Studies evaluating interactions between freshwater fish farms and rivers are limited; therefore, we conducted a systematic review and an appraisal of evidence quality to assess the impacts of salmonid fish farming on river water quality. The review revealed that two main types of water quality indicators are generally applied: physicochemical and biological. The response variables used to determine the effects of fish farm effluent on water quality vary considerably, yet most studies indicate that aquaculture negatively affects the environment. Overall, we highlight the knowledge gaps, including a lack of studies in freshwater aquaculture hotspots. The effects of fish farming on bacterial communities are also not clear due to limited research on these bioindicators. We suggest improvements in study design, including thorough consideration of confounding factors, and the provision of background information on the fish farms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of rarity form on species’ responses to land use - Louise Sykes; Luca Santini; Adrienne Etard; Tim Newbold (Conservation Biology, 2020)
Anthropogenic land‐use change causes substantial changes in local and global biodiversity. Rare and common species can differ in sensitivity to land‐use change; rare species are expected to be affected more negatively. Rarity may be defined in terms of geographic range size, population density, or breadth of habitat requirements. How these 3 forms of rarity interact in determining global responses to land use is yet to be assessed. Using global data representing 912 vertebrate species, we tested for differences in responses to land use of species characterized by different types of rarity. Land‐use responses were fitted using generalized linear mixed‐effects models, allowing responses to vary among groups of species with different forms of rarity. Species considered rare with respect to all 3 forms of rarity showed particularly strong declines in disturbed land uses (>40% of species and 30% of individuals in the most disturbed land uses). In contrast, species common both geographically and numerically and with broad habitat requirements showed strong increases (up to 90% increase in species and 40% in abundance in some land uses). Our results suggest that efforts to understand the vulnerability of species to environmental changes should account for different types of rarity where possible. Our results also have potentially important implications for ecosystem functioning, given that rare species may play unique roles within ecosystems.

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.